2018
DOI: 10.3389/fpsyg.2018.01215
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy, Flow, Affect, Worry and Performance in Elite World Cup Ski Jumping

Abstract: The present study investigated the relationship between self-efficacy, flow, positive- and negative affect, worry and ski jumping performance, as well as the degree of influence these psychological factors have on ski jumping performance in specific competitions and overall World Cup ranking. World Cup ski jumpers (N = 40) responded to four questionnaires in the middle of the World Cup season, reporting their subjective experience during a competitive setting over a period of three consecutive days. Social Cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 30 publications
4
35
2
Order By: Relevance
“…Another scholarly research of Sklett, Loras, & Sigmundsson (2018), of sports context revealed that Selfefficacy was moderately affect to ski jumping performance (Sklett, Lorås, & Sigmundsson, 2018) which is consistent with the present study..…”
Section: Discussionsupporting
confidence: 91%
“…Another scholarly research of Sklett, Loras, & Sigmundsson (2018), of sports context revealed that Selfefficacy was moderately affect to ski jumping performance (Sklett, Lorås, & Sigmundsson, 2018) which is consistent with the present study..…”
Section: Discussionsupporting
confidence: 91%
“…Regarding repetitive thinking, firstly a direct relationship between rumination and action orientation in competitive athletes has been demonstrated (Kröhler & Berti, 2019 ). Secondly, between 27 and 36% of the variance in ski flying results could be accounted for by the amount of worry (Sklett, Loras, & Sigmundsson, 2018 ). However, until now the concepts of self-compassion and repetitive thinking have not been related in the sport context.…”
Section: Self-compassion and Repetitive Thinking In Athletesmentioning
confidence: 99%
“…The analysis of psychological factors that may influence the performance of athletes has been a subject of study in recent decades in numerous disciplines [1][2][3]. There is a growing understanding of how aspects such as competitive anxiety, motivation, moods, flow states, and self-efficacy relate to each other [4,5]. Thus, in the training processes of athletes, the assessment of their psychological functioning is a dimension that is increasingly being integrated into their global preparation [6,7].…”
Section: Introductionmentioning
confidence: 99%